The Effect of Perceived Quality and Brand Image on Sriwijaya Air Ticket Purchase Decisions Periods January – July 2022 - Sidjabat, Sonya; Fadillah, Ine (Institut Transportasi dan Logistik Trisakti, 2022)
Airlines in Indonesia compete each other to attract people's attention to use their services. The purpose of this study to analyze the effect of perceived quality and brand image on the purchase decision of Sriwijaya Air airline tickets for the period January - July 2022. This study uses quantitative methods. The sampling technique used is simple random sampling with 120 respondents and the data were processed using SPSS version 26. Data were analyzed by validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, coefficient of determination test (R2), t test, and F test. Based on the results of the analysis and discussion for perceived quality and brand image on purchase decision, the t test shows that tcount > ttable which states that the perceived quality and brand image has a positive and significant effect on purchase desicion for Sriwijaya Air airline tickets. F test show that the value of Fcount > Ftable partially perceived quality and brand image has a positive and significant effect on the purchase desicion for Sriwijaya Air tickets.